Determining People's Design Priorities for Neighbourhood Units: A Study in Liverpool, Merseyside - Sinan Levend; Thomas B. Fischer (Iconarp International Journal of Architecture and Planning, 2022)
Local planning authorities and developers aim at designing and regenerating neighbourhoods in which people want to live. However, this aim is difficult to achieve if participation is conducted poorly. As a result, people may live in places that are created according to the ideas of designers and the priorities of market conditions and not according to their own. Therefore, determining people's preferences is essential for livable and sustainable neighbourhood design. This paper introduces and tests a method for determining people's design preferences, namely an Analytic Hierarchy Process (AHP) methodology. The method is based on making pairwise comparisons of key design principles and structural factors of neighbourhood units. The testing was conducted in Liverpool city centre. Here, it was established that participants' priorities in neighbourhood design are safety, affordable housing and accessibility, respectively. Also, participants prefer to live in non-gated detached and semi-detached housing communities. This article offers an empirical contribution to the participatory neighbourhood planning literature.